RSSDI textbook of diabetes mellitus - Tripathy, BB (Jaypee Brothers Medical Publishers, 2012)
In the course of the last few decades, India has emerged as the country with the highest number of patients with deabetes. In keeping withthis, in india diabetology has emerged as a major specialty in the practice of both general medicine and endocrinology. Over the last thirty years, several centers have adpted diabetes as a single disease specialty for the state of the art investigations and clinical care.